TUBERCULOUS LYMPHADENITIS IN CHILDREN –14 YEARS OF EXPERIENCE - Boskovska, Katerina; Ivanovska, Julija; Nestorov, Hristijan; Popova, Gorica; Petlichkovska, Sandra; Arnaudova - Danevska, Ivana; Chakalarovska, Irena (Journal of Morphological Sciences; Vol 6 No 2 (2023): JMS, 2023)
Tuberculosis (TB)is a major public health problem worldwide. It is one of the main causes of infectious disease and mortality, especially in developing countries. Extra pulmonary tuberculosis accounts for 15-20 % of all types of tuberculosis. Lymph nodes are the second most common localization after pleural TB. In childhood, the most commonly envolved  are the hilar lymph nodes. Material and methods: We analyzed the frequency of tuberculous lymphadenitis in children treated at the Institute for respiratory diseses in children-Kozle, in the last 14 years. From January 2006 to February 2020 , weâ€™ve treated  397 children with  TB. 55 of them (13,8%), were with tuberculous lymphadenitis. Female children were 34 (61%), the others were   male.The most frequent was hilar lymphadenitis at 40 (72%), second  localization were cervical lymph nodes in 10( 18%). There was 1 child with submandibular localization,1 supraclavicular, 2children with axillary lymphadenitis and one with mesenterial lymphadenitis. Most of the patients had contact with TB. The diagnosis was confirmed pathohistological in the patients with peripheral lymphadenitis. Tuberculosis treatment was started in all patients based on clinical criteria, exposure, positive TST, chest X-ray, or histological confirmation. All of the patients have finished the treatment successfully.  Tuberculous lymphadenitis can be a diagnostic and therapeutic challenge in children. Early diagnosis and timely initiation of therapy lead to favorable therapeutic outcome and reduce complications. Key words: tuberculosis, children,  lymphadentis.